Originally Posted by

**Jhevon** i would like to say first of all that the manner in which you post is confusing, please fix it.

i suppose you started with 3x + 2 - 6x = 8 + 3(x + 2) .........(you should have started a new line here, you made it look like you were multiplying by 3(x + 2), do you see that?)

anyway, we get

2 - 3x = 8 + 3x + 6 ..............expanded the brackets on the right

=> 2 - 3x = 14 + 3x .............simplified both sides

=> 2 - 14 = 3x + 3x .............added 3x - 14 to both sides

=> -12 = 6x .......................simplified both sides

=> x = -2 ..........................divide both sides by 6